Surface engineering of a 2D CuFe-LDH/MoS2 photocatalyst for improved hydrogen generation - Vennapoosa C.S.; Shelake S.P.; Jaksani B.; Jamma A.; Moses Abraham B.; Sesha Sainath A.V.; Ahmadipour M.; Pal U. (Royal Society of Chemistry, 2025)
Creating effective heterostructure photocatalysts with S-scheme-based charge-transfer dynamics enables efficient electron transfers, thereby enhancing visible-light-induced photocatalytic hydrogen production. In this report, we investigate a series of CuFe-LDH/MoS2 composites synthesized by employing MoS2 with CuFe-LDH through a self-assembled chemical method and an in situ hydrothermal process. The morphological features illustrate a consistent stacked nanosheet-like structure. The enhanced electronic and optical properties of the as-prepared CuFe-LDH/MoS2 and their improved photocatalytic hydrogen evolution execution is credited to the S-scheme heterojunction preventing the recombination of photogenerated charge transporters and improving the fast charge transference and utilization. The CuFe-LDH/MoS2 photocatalyst exhibits a superior photocatalytic H2 creation rate of 3.4 mmol g?1 h?1 and an AQY of 1.3% compared to CuFe-LDH (1.3 mmol g?1 h?1; AQY:0.5%). DFT studies reveal that the synergistic effects of the CuFe-LDH/MoS2 interface effectively enhance both the thermodynamics and kinetics of the rate-determining step for the hydrogen evolution reaction, which aligns with the experimental results. This design approach paves the way for creating highly efficient photocatalysts for future research in this promising domain. ? 2024 RSC.